Circ_0003645 serves as miR-335-5p sponge to promote the biological process of diffuse large B-cell lymphoma by upregulating NFIB. (17th February 2022) - Lin, Dayi; Wang, Ya; Lei, Linian; Lin, Congmeng
Abstract: Background: Circular RNAs (circRNAs) are critical regulators for the development of many tumours, including diffuse large B-cell lymphoma (DLBCL). However, the role and mechanism of circ_0003645 in DLBCL progression remains obscure. Methods: Quantitative real-time PCR was performed to measure the expression of circ_0003645, microRNA (miR)-335-5p and nuclear factor I/B (NFIB). Cell viability, apoptosis and cell cycle were measured by cell counting kit 8 assay and flow cytometry. Protein expression was assessed using western blot analysis, and cell glycolysis was evaluated by detecting glucose consumption and ATP/ADP ratios. Besides, dual-luciferase reporter assay and RIP assay were used to confirm RNA interaction. Results: Our data showed that circ_0003645 expression was significantly upregulated in DLBCL tumour tissues. After circ_0003645 knockdown, the viability, cell cycle and glycolysis of DLBCL cells were inhibited, while cell apoptosis was promoted. MiR-335-5p could be sponged by circ_0003645, and NFIB was confirmed to be a downstream target of miR-335-5p. Function analysis revealed that anti-miR-335-5p reversed the regulation of si-circ_0003645 on DLBCL cell progression, and NFIB overexpression also abolished miR-335-5p-mediated the biological functions of DLBCL cells. Conclusion: The present study revealed that circ_0003645 promoted the proliferation and glycolysis of DLBCL cells by the miR-335-5p/NFIB axis, which might provide a novel insight for DLBCL treatment.